Run to shelter or bury into the sand? Factors affecting escape behaviour decisions in argentinian sand dune lizards (Liolaemus multimaculatus) - Kacoliris, Federico Pablo (2009)
Fil: Kacoliris, Federico Pablo. División Herpetología. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina